Analisis Harga Saham PT Astra Internasional Tbk Menggunakan Data Dari Bursa Efek Indonesia dalam Jangka Waktu Pendek Menggunakan Metode Naïve Bayes dan Decision Tree-J48 - Heima Sitorus; Yusran Tarihoran (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Stock price prediction is a very necessary action as a first step to taking the decision to determine when to transact a sale and purchase of existing shares in Indonesia stock exchange. Stock price prediction is done using two methods are compared, i.e.; Naїve Bayes method and the method of Decision Tree-J48. The amount of data used is as much as 1,195 and data used as the data for testing is as much as 20% or 239 the data. As a result of the level of accuracy of the Naïve Bayes Method using data testing is 92.0502%. With the presentation for the value of precision or accuracy of information expected by the author with the answers given by the system of 0920 and the value for the recall or the success rate of taking action against information found by the system of 0.961. While the results of a prediction using Decision Tree J-48 results for accuracy using data testing is 98.7448%. %. With the presentation for the value of precision or accuracy of information expected by the author with the answers given by the system. of 0.989 and value for the recall or the success rate of taking action against information found by the system of 0.997.